Principals’ Managerial Styles As Determinat of Public Senior Secondary School Efectiveness in Kwara State - Adam Ishola Mustapha; Kikelomo .W. Sallee; Alao Busayo Oluwabukola (Indonesian Journal of Education and Social Sciences, 2023)
Education is a basic rights and the needs for its provision in most efficient manner towards ensuring social liberation, political, economic and cultural development of countries cannot be undermined. However, the efficacy of secondary schools has raised deep concern among stakeholders in the sector. Thus, the study examines principals’ managerial styles as determinant of public senior secondary schools school effectiveness in Kwara State. Nigeria. Descriptive research design of correlation type was adopted for this study. The population of the study was made up of 6, 483 teachers and 384 principals in all the 384  public senior secondary schools in the three senatorial districts that constitute Kwara State (Kwara Central, Kwara North and Kwara South). Ten public senior secondary schools were randomly selected from each of the three senatorial districts that make up the Kwara State, thus 30 public senior secondary schools were selected for the study. Also, 279 teachers were selected using Research Advisor (2006), Managerial Styles and School Effectiveness Questionnaires (PMSSEQ) were designed for the collection of relevant data from the repondents. The instruments were validated and subjected to reliability study. The data gathered for the study were statistically analyzed using descriptive research statistic of frequency, percentage answer the research questions, while Pearson Product – Moment Correlation was used to answer the second research question. The findings of the study revealed that principals’ managerial styles determined school effectiveness in public senior secondary school in Kwara state. It was recommended among others that: capacity buildings through seminars, workshops and conferences should be periodically organized for secondary school principals to update their managerial knowledge and skills on global leadership styles thereby enhancing effectiveness of the schools. Also, principals’ should not restrict themselves to just one managerial style of leadership, but rather varying them depending upon the circumstances for overall improvement and effectiveness of the school system.